The Effect of Thymus Vulgaris Extract on Smooth Muscle Relaxation of Guinea Pig Aortic Ring: Study In Vitro - Muhammad Basheer Abdullah Alsubbi (Journal of Global Pharma Technology, 2019)
Objective: Hypertension appears to have a complex association with endothelial dysfunction. One of herbs that potential to develop as anti hypertension is Thymus vulgaris which contains high concentrations of phenols, including thymol and carvacrol that offer protection from hypertension. This study aimed to prove the correlation between different concentration of Thymus vulgaris extract and response of aortic ring relaxation. Methods: Using a laboratory experiment (in vitro study), treatment with provision doses of Thymus vulgaris extract was conducted to guinea pig (aorta ring) after pre-contracted by phenylephrine (PE). Thymus vulgaris extract (TM) at the doses of 0.0625, 0.125, 0.25, 0.5 and 1% were administered to experimental groups including 5 doses of extract with intact aorta rings and 5 doses of extract with denuded aorta rings. Pearson correlation test and T-test were used to analyzed the data. Results: The results indicate that administration of Thymus vulgaris extract can decrease the contraction of aorta guinea pig. Different doses of Thymus vulgaris extract have different relaxation responses of smooth muscle cell in aortic rings of guinea pig. The lower concentrations doses of Thymus vulgaris extract (0.0625% and 0.125%) can cause an effective and better relaxation effect on contraction of smooth muscle in denuded aorta than in intact aorta. Conclusion: The higher concentrations doses of Thymus vulgaris extract (0.025%, 0.5% and 1%) can increase the contraction of smooth muscle for both intact and denuded aorta of guinea pig.Keywords: Thymus vulgaris, intact aorta rings, denuded aorta rings, phenylephrine